Observation of the decay B → J/ψK and search for X(3872)→ J/ψ - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2004)
The observation of charmonium production in B meson decays by color-supressed b → cc̄s quark transition was discussed. The data used in the observation correspond to a integrated luminosity of 81.9 fb -1 taken on the γ(4S) resonance. The data were collected at the asymmetric energy e+e- storage ring with BABAR detectors. The results show that with an upper limit of X(3872) in the product branching fraction the magnitude of possibole enhancements with charmonium hybrid states can restrict.